The Influence of Bi Rate, Car, and CCYB Policy on Bank Stability in Indonesia - Diah Intan Pratiwi; Tiara Nirmala; Thomas Andrian; Nurbetty Herlina Sitorus (Departement of Mathematics Education, 2024)
This study is to examine how Indonesian bank stability (Z-Score) is affected by the BI Rate, CAR, and CCyB policy. Multiple regression analysis employing the Random Effect Model (REM) method is the technique employed. The study's findings indicate that, in part, the CAR, CCyB, and BI Rate policies have a positive and significant impact on bank stability in both Large Banks and Small Banks between 2010 and 2022. In addition, from 2010 to 2022, the BI Rate, CAR, and CCyB policies will all have a major impact on the stability of banks, both Large Banks and Small Banks. Aside from that, the Independent Sample T-Test results indicate that there are significant differences in the stability of banks, where Large Banks being more stable than Small Banks. Additionally, the differences is caused by bank sensitivity, where Small Banks being more influenced than Large Banks in the impact of the BI Rate, CAR, and CCyB policy variables on bank stability between 2010 and 2022.